Ruxolitinib for the management of myelofibrosis: Results of an international physician survey - Ellis, Martin H. (Leuk Res, 2017)
BACKGROUND: Ruxolitinib is established as treatment for symptomatic myeloproliferative neoplasm (MPN)-associated myelofibrosis. The strict inclusion and exclusion criteria and dose modification rules that applied to the COMFORTI and II studies that led to the licensing of ruxolitinib are not always applicable to routine clinical practice. Thus physicians now face decisions regarding ruxolitinib use that were not addressed in these pivotal trials. METHODS: We performed an online survey of hematologists practicing in Europe, Israel, the United Kingdom and the United States. Demographic details regarding the physicians and their practice as relates to MPNs were collected. Management decisions pertaining to the use of ruxolitinib were obtained regarding 10 clinical scenarios relating to anemia, thrombocytopenia, frailty, infection and lack or loss of response to ruxolitnib in MF patients. RESULTS: 140 physicians responded to the survey. There were marked differences regarding their decisions for ruxolitinib administration in MF patients with or developing anemia or thrombocytopenia. Similarly there was little consensus regarding management of patients refractory or losing a response to ruxolitinib. There were differences between “MPN-focused” and “non-MPN-focused” physicians in certain areas. CONCLUSION: Physician practices regarding management of MF patients experiencing ruxolitinib-related toxicities or in whom response to the drug is lost was variable. This was true of “MPN-focused” and “non-MPN-focused” physicians in certain cases. Physician education and experience in using ruxolitinib may improve patient management.